2023
DOI: 10.1126/sciadv.ade9118
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution vibrational imaging based on photoswitchable Raman probe

Abstract: Super-resolution vibrational microscopy is promising to increase the degree of multiplexing of nanometer-scale biological imaging because of the narrower spectral linewidth of molecular vibration compared to fluorescence. However, current techniques of super-resolution vibrational microscopy suffer from various limitations including the need for cell fixation, high power loading, or complicated detection schemes. Here, we present reversible saturable optical Raman transitions (RESORT) microscopy, which overcom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The SRS signal intensity at 1503 cm -1 exhibited a more than 25-fold change during this photoswitching process, underscoring the effective control of the Raman signal with the CW light. We calculated the relative Raman intensity versus EdU (RIE) value for the closed form of DAE620 to be 9.78, which surpasses the RIE values of CMTE (RIE: 1.43) 26 . The high SRS signal intensity of DAE620 is attributed to the epr effect due to the longer absorption wavelength.…”
Section: Design Of Bright Photoswitchable Raman Probe For Resort Imagingmentioning
confidence: 94%
See 3 more Smart Citations
“…The SRS signal intensity at 1503 cm -1 exhibited a more than 25-fold change during this photoswitching process, underscoring the effective control of the Raman signal with the CW light. We calculated the relative Raman intensity versus EdU (RIE) value for the closed form of DAE620 to be 9.78, which surpasses the RIE values of CMTE (RIE: 1.43) 26 . The high SRS signal intensity of DAE620 is attributed to the epr effect due to the longer absorption wavelength.…”
Section: Design Of Bright Photoswitchable Raman Probe For Resort Imagingmentioning
confidence: 94%
“…Recently, photoswitchable SRS spectroscopy and microscopy [29][30][31] have been achieved by leveraging photochromic molecules that can transition between two distinct isomers when exposed to ultraviolet (UV) or visible light, thereby enabling the control of Raman signal emission. Inspired by the principles of RESOLFT microscopy, we introduced the concept of RESORT microscopy 26 , wherein an additional continuous-wave (CW) laser beam, configured in a donutshaped pattern, is employed to modulate the SRS detection of a photoswitchable Raman probe (see Fig. 1).…”
Section: Resort Microscopy Based On Photoswitchable Srsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking advantage of chemical engineering, photoswitchable SRS microscopy has been developed based on photoreaction or photoisomerization of vibrational probe molecules. 65−67 Further integrated with the reversible saturable/switchable optical fluorescence transition (RESOLFT) strategy, Shou et al 68 and Ao et al 69 reported super-resolution SRS nanoscopy with sub-100 nm optical resolution. In this scheme, a Gaussianshaped ultraviolet (UV) activation beam and a donut-shaped visible depletion beam were implemented to confine the final SRS point spread function (PSF) (Figure 2e).…”
Section: Developments Of Srs Microscopymentioning
confidence: 99%